Sororidade - para que e para quem? - Pschichholz, Roberta (2025)
It was during the feminist movement of the late 1960s and early 1970s that sorority (Sisterhood) became consolidated as a way of expressing collective gender identities and demanding political solidarity among women. The slogan “Sisterhood is Powerful!” (1967) became a collective ideal of resistance (MORGAN, 1970). This collectivity, however, was limited to white, middle-class women engaged in fighting for sexual and reproductive rights, equal pay and professional opportunities, the end of domestic violence, and patriarchal oppression. In short, it was a universalizing and white discourse that did not include Black or decolonial feminists (HOOKS, 1981) and disregarded the intersectional perspective that shapes women’s trajectories. Co-opted by capitalism, sisterhood became emptied of meaning as a movement for the unification and empowerment of women as an oppressed group (FRYE, 1983). The same occurred with terms such as empowerment and female entrepreneurship. But, after all, does it make sense to speak of sisterhood today? What social project would it serve? And for whom? Is it possible to speak of a universal sisterhood? Based on a historical investigation of women’s relationships, the concept of gender oppression, and the understanding of sisterhood from the perspectives of different scholars, I propose that, just as there are multiple feminisms, there are also diverse ways of establishing sisterhood.